(untitled) (Bangladesh Medical Journal Khulna, 2016)
Amoebic liver abscess is an important cause of space occupying lesions of the liver, especially in tropical and sub tropical regions. It is the most frequent complication of invasive amebiasis. It may be found in all age groups but relatively rare in children. The signs and symptoms vary according to the severity of illness. The present study was done to evaluate the clinical profile of patients with amoebic liver abscess for age, gender, clinical features, site of abscess, number of abscess, treatment modality by intravenous metronidazole along with percutaneous needle aspiration and prognosis. A prospective study of 86 admitted patients of amoebic liver abscess were included in this study which was carried out in the medicine department of Khulna Medical College Hospital over a period of 2 years from July 2010 to June 2012. Mean age of patients was 45 years. Male female ratio was 7:1. The mean duration of fever was 17.9 days and the mean duration of pain was 14.1 days. The duration of fever for more than 2 weeks was seen in 38 cases. Regarding clinical features, the major symptoms of fever, pain abdomen and dysentery were seen in 81, 78 and 10 cases respectively. The major signs as determined by clinical and radio imaging studies were hepatomegaly in 76, right lobe abscess in 60, left lobe abscess in 12, multiple abscesses in both lobes in 18, ascites in 5 and right sided pleural effusion in 12 cases respectively. All the cases underwent percutaneous needle aspiration. 5 cases died out of 86 patients. Bang Med J (Khulna) 2015; 48 : 20-23